2012
DOI: 10.1002/jcp.22943
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous fibroblast‐derived pericyte recruitment in a human tissue‐engineered angiogenesis model in vitro

Abstract: Cooperation between endothelial cells and pericytes is essential to the stabilization and maturation of blood microvessels. We developed a unique in vitro tissue-engineered model to study angiogenesis. The human endothelialized reconstructed connective tissue model promotes the formation of a three-dimensional branching network of capillary-like tubes (CLT) with closed lumens. The purpose of this work was to investigate whether pericytes were spontaneously recruited around CLT in the model. We demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…Since there were no pericytes in our cultured conditions, this step was inferred by basement membrane formation around the CLS. Berthod et al 27 showed that the pericytes could derive from fibroblast in vitro , which encouraged us to investigate the same effect with our model. The CLSs in psoriatic skin models are more numerous, complex, branched, dense, and chaotic than in healthy substitutes.…”
Section: Discussionsupporting
confidence: 53%
“…Since there were no pericytes in our cultured conditions, this step was inferred by basement membrane formation around the CLS. Berthod et al 27 showed that the pericytes could derive from fibroblast in vitro , which encouraged us to investigate the same effect with our model. The CLSs in psoriatic skin models are more numerous, complex, branched, dense, and chaotic than in healthy substitutes.…”
Section: Discussionsupporting
confidence: 53%
“…These cells are both NG2 + and PDGFR-β + (Fig. 1f), consistent with a pericyte phenotype1718. Once established, the vessels rapidly lay down a collagen IV-rich basement membrane (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…To better quantify the specific angiogenic potential of each neurotrophic factor, we investigated their effect on CLT formation in vitro using our well-characterized tissue-engineered model of angiogenesis. [30][31][32] We demonstrated a major increase in the number of CLT for all neurotrophic factors. Indeed, NGF, GDNF, and NT-3 induced a 40% to 80% increase in the number of CLT.…”
Section: Blais Et Almentioning
confidence: 74%